Efficacy of Baduanjin for obesity and overweight: a systematic review and meta-analysis - Gao, Hainan; Li, Xue; Wei, Hongnan; Shao, Xinxin; Tan, Zili; Lv, Shaowei; Pan, Lijie; Yu, Ting; Ye, Qiuyan; Zhang, Haibo; Zhu, Xiangyu (Frontiers in Endocrinology, 2024)
Background According to data from the World Health Organization (WHO), there is a significant public health issue regarding the increasing number of individuals affected by obesity and overweight on an annual basis. Therefore, it is imperative to urgently identify interventions that can effectively control and improve this condition. Baduanjin, as a medium-intensity exercise, appears a suitable approach for weight reduction among individuals with obesity. This paper aimed to provide a systematic review and meta-analysis of the efficacy of Baduanjin in addressing obesity and overweight, with the ultimate goal of assisting individuals with obesity in finding an effective, safe, and engaging method for weight reduction. Methods We conducted a comprehensive search of multiple databases including PubMed, Cochrane Library, Web of Science, Embase, The China National Knowledge Infrastructure (CNKI), The Chinese Scientific Journal Database (VIP), The Chinese Biomedical Literature Database (CBM), and WanFang Database to identify relevant articles published from the inception of each database until September 2023. Specifically, we focused on randomized controlled trials (RCTs) investigating the effects of Baduanjin on weight reduction. Data from these studies were extracted and analyzed using appropriate statistical methods. In cases where there was no significant heterogeneity (I2 < 50%, p > 0.1), we employed a fixed effects model for data synthesis; otherwise, a random effects model was selected. Funnel plots were used to assess publication bias, and the mean difference (MD) was reported as an indicator of treatment group differences. Results A total of 420 participants were included in 10 studies. The MD results of the experimental group when compared with the control group were −3.69 (95%CI = −4.97 to −2.40, p < 0.001) for body weight (BW), −5.42 (95%CI = −6.56 to −4.28, p < 0.001) for body mass index (BMI), −1.36 (95%CI = −1.76 to −0.96, p < 0.001) for waist circumference (WC), −3.40 (95%CI = −4.43 to −2.37, p < 0.001) for hip circumference (HC), and −0.03 (95%CI = −0.04 to −0.02, p > 0.1) for the waist-to-hip ratio (WHR). All of the values in the experimental group showed significant difference. The results of the Egger’s test (t = 1.43, p = 0.190) suggest that there was no substantial bias present within the data analysis process. The safety profile revealed no adverse events reported across all 10 studies. Conclusion Baduanjin could be effective in reducing weight, and the practice of Baduanjin has the potential to regulate BW, BMI, WC, HC, and WHR. However, further well-designed RCTs are still necessary to provide more robust evidence in the future. Systematic review registration http://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024513789.